Thematic Interpretation Analysis of the Environment and Ecological Crisis from an Islamic Perspective - Samar A. El-Farra (CV Edujavare Publishing, 2025)
Environmental degradation and ecological crises have become global challenges affecting human life, biodiversity, and the sustainability of natural resources. Climate change, deforestation, pollution, excessive exploitation of natural resources, and ecological imbalance increasingly threaten social stability and environmental sustainability worldwide. In Islamic teachings, the environment is viewed as a divine trust (amanah) that must be protected and managed responsibly by humans as stewards (khalifah) on earth. This study aims to analyze environmental and ecological issues through thematic interpretation (tafsir maudhu’i) from an Islamic perspective and examine the relevance of Qur’anic teachings to contemporary ecological crises. The research employs a qualitative descriptive approach through literature review and thematic analysis of Qur’anic verses, Hadith, and scholarly interpretations related to environmental ethics, ecological balance, and human responsibility toward nature. The findings indicate that Islam strongly emphasizes environmental preservation, moderation in resource utilization, prohibition of environmental destruction, and ethical responsibility toward all living beings. Qur’anic teachings concerning balance (mizan), stewardship, sustainability, and justice provide important ethical foundations for addressing modern ecological crises. The study also reveals that environmental damage is closely connected to human greed, consumerism, and irresponsible exploitation of natural resources. Therefore, strengthening ecological awareness through Islamic ethical values and environmental education is essential for promoting sustainable development and environmental responsibility in contemporary society.